A comparative study of portoenterostomy and choledochojejunostomy in New Zealand rabbits under immunosuppression - Sun, Jiuzheng; Zhang, Haiming; Huang, Hao; Qu, Wei; Zhu, Zhi-Jun (Frontiers in Surgery, 2025)
BackgroundThis study aims to evaluate the safety and feasibility of performing portoenterostomy in rabbits under immunosuppressive therapy.Methods49 New Zealand rabbits were randomly divided into two groups: the experimental group (n = 24) underwent portoenterostomy, while the control group (n = 25) received traditional choledochojejunostomy. Postoperatively, all rabbits were administered oral methylprednisolone and cyclosporine A. Four rabbits from each group were sacrificed on postoperative days 30, 60, and 90. Primary outcomes included postoperative mortality, morbidity, and pathological changes at the anastomotic site. Secondary outcomes encompassed biochemical indicators such as ALT, AST, ALB, ALP, GGT, DBIL, TBIL, TBA, BUN, and Scr.ResultsIn a study comparing portoenterostomy and choledochojejunostomy, 49 rabbits underwent surgery (24 in the portoenterostomy group and 25 in the choledochojejunostomy group). The postoperative mortality rates were 4/24 in the portoenterostomy group and 6/25 in the choledochojejunostomy group. Changes in serum bilirubin and creatinine levels suggested the occurrence of anastomotic stricture, cholangitis, and renal dysfunction in some rabbits. The portoenterostomy group showed less severe anastomotic stricture compared to the choledochojejunostomy group, and the use of immunosuppressive agents did not negatively affect the healing process. Pathological observations indicated good healing outcomes within 1 to 3 months postoperatively, despite the presence of inflammation and scar formation.ConclusionsThe study demonstrates that small portoenterostomy performed under immunosuppressive therapy is a safe, simple, and technically feasible surgical approach.